Sim Card Alarm for Android Smartphone - Rikip Ginanjar; Ridho Utomo (ULTIMA InfoSys, 2016)
Since the first Android smartphones were released, many applications have been developed until today. One of them is security application. Security applications consist of several types of applications such as Antivirus, SIM Card Change Alarm, and Applocker. SIM Card Changed Alarm is a security application that has capability to monitor SIM Card change in Android smartphones. Although there are many SIM Card Change Alarm applications which are available in Google Playstore, there are many people who are not satisfied with this applications. It happens due to them only sends the SMS alert to the owner without locking the phone to prevent other people using it. The outcome of this research will have the same feature as SIM Card Change Alarm but with additional features such as locking the smartphone if the SIM Card has been changed, locking and unlocking remotely using SMS, triggering loud alarm, and calling-back to owner when the smartphone has been lost or stolen. The outcome expected for the Prifone Application is a userfriendly application which could be used by many people around the world and also is able to secure Android smartphones. Index Terms – android, sim card alarm, security application